Hazard Analysis Critical Control Point (HACCP) Sebagai Model Kendali Dan Penjaminan Mutu Produksi Pangan - Cartwright, Lien Maulina; Latifah, Diah (INVOTEC, 2010)
This research is basically based on the premise that food security especially in the field of pastry making into something very important. The purpose of this study are: 1) to analyze important stages in the processing of pastry to ensure the quality of pastry; 2) Evaluate how the supervision and quality control in the processing of pastry, and 3) evaluate the basic feasibility and level of implementation of HACCP Processing Unit pastry. This research use descriptive method. In collecting observations and interviews. The results give an idea as follows: 1) The stages in the processing Pastry has adopted 7 principles of HACCP; 2) Supervision and quality control in the manufacture of pastry is in compliance with the HACCP concept, 3) the basic feasibility and level of implementation of HACCP in the processing of consecutive Pastry as follows: good, good and excellent.